Collaborative Management as a Catalyst for Artificial Intelligence Adoption in Elementary Education: A Case Study - Nenden Kurniati; Sri Handayani (Journal of Science and Education (JSE), 2026)
This study examines the optimization of collaboration between school principals and school committees as a strategic catalyst for the adoption of Artificial Intelligence (AI) technologies in elementary schools. The research addresses the critical need for digital transformation in primary education, particularly within resource-constrained environments, emphasizing that technology adoption hinges on effective multi-stakeholder management. Employing a qualitative case study methodology (Creswell, 2014) at two Indonesian elementary schools, data were collected through in-depth interviews, observation, and document analysis. The findings are structured around the POAC framework (Robbins & Coulter, 2020), revealing that structured collaboration facilitates three strategic objectives: participatory planning of AI integration, adaptive policy implementation that addresses digital literacy gaps, and data-driven monitoring for accountability. The study concludes that formalized, sustained principal-committee collaboration accelerates AI adoption, strengthens institutional adaptability, and mitigates cultural resistance, positioning it as an essential model for systemic digital readiness.